Association Between Steady-State Lactate Dehydrogenase Levels and Sickle Cell Complications: A Systematic Review - Mohamed, Sagad O.O.; Mohammed, Amged; Salih, Fatima S.K.; Elgadal, Hozifa A.M.; Elsamany, Ayman A.A.; Salih, Mohamed S.K.; Mustafa, Huda M.A.; Elawad, Israa; Ahmedkaroum, Mona G.A.; Saeed, Safaa G.A.; Ibrahim, Rowa E.A.; Mohamedien, Esraa A.; Babiker, Aya A.H.; Suliman, Esraa T.; Mohamed, Eman O.E. (Avicenna Journal of Medicine, 2025)
Sickle cell disease (SCD) is a hereditary hemoglobin disorder characterized by vaso-occlusion and chronic hemolysis, leading to severe complications. Finding cost-effective and reliable biomarkers for predicting disease severity and identifying high-risk patients remains challenging, especially in resource-limited settings. This systematic review evaluates the association between lactate dehydrogenase (LDH) levels measured during clinical steady-state and various complications of SCD to assess its prognostic value. A systematic literature search, adhering to PRISMA guidelines, was conducted across Medline/PubMed, Web of Science, Embase, and ScienceDirect. Eligible studies included all observational studies examining the relationship between LDH levels and subsequent SCD complications. The statistical analyses were performed to calculate the pooled standardized mean difference (SMD) and its 95% confidence interval (CI). A total of 34 studies were included, highlighting significant associations between elevated LDH levels and various SCD-related complications. These included pulmonary arterial hypertension (SMD = 0.454, 95% CI: 0.032–0.875, p = 0.035), stroke risk through transcranial Doppler velocities (SMD = 0.651, 95% CI: 0.459–0.843, p < 0.001), and kidney involvement (SMD = 0.399, 95% CI: 0.014–0.785, p = 0.042). This systematic review reveals a consistent association between elevated steady-state LDH levels and major complications of SCD. The findings suggest a potential role for LDH as a readily available biomarker for SCD severity, underlining its potential for inclusion in clinical assessments of SCD severity, risk stratification, and tailored interventions for high-risk patients.
Keywords: sickle cell disease; complications; lactate dehydrogenase; systematic review